2018
DOI: 10.1002/pbc.27539
|View full text |Cite
|
Sign up to set email alerts
|

Only strongly enhanced residual FDG uptake in early response PET (Deauville 5 or qPET ≥ 2) is prognostic in pediatric Hodgkin lymphoma: Results of the GPOH‐HD2002 trial

Abstract: Purpose In 2014, we published the qPET method to quantify fluorodeoxyglucose positron emission tomography (FDG‐PET) responses. Analysis of the distribution of the quantified signals suggested that a clearly abnormal FDG‐PET response corresponds to a visual Deauville score (vDS) of 5 and high qPET values ≥ 2. Evaluation in long‐term outcome data is still pending. Therefore, we analyzed progression‐free survival (PFS) by early FDG‐PET response in a subset of the GPOH‐HD2002 trial for pediatric Hodgkin lymphoma (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…To restrict interim analysis to a single scan, while maintaining the advantage of a continuous scale, we developed the qPET method (q, quotient) where the mean SUV of the four most intense connected voxels of residual lymphoma-related uptake are put into relation with the mean SUV of a large volume in the liver. Pioneered in Hodgkin's lymphoma, this approach converted the ordinal Deauville scale into a well-defined quantitative scale (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…To restrict interim analysis to a single scan, while maintaining the advantage of a continuous scale, we developed the qPET method (q, quotient) where the mean SUV of the four most intense connected voxels of residual lymphoma-related uptake are put into relation with the mean SUV of a large volume in the liver. Pioneered in Hodgkin's lymphoma, this approach converted the ordinal Deauville scale into a well-defined quantitative scale (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…o Hypofractionation (!3 Gy/f) has been used to treat metastatic STS and ES, achieving high levels of local control[24] (level 3). o SBRT has demonstrated good local control in small single centre series[25]; it is being evaluated in the French SBRT study (see above), and the COG AEWS1221 Ewing study where 30-40 Gy in 5 fractions is being used for bone metastases (level 3).Evidence o Most protocols for the treatment of paediatric Hodgkin lymphoma have used 1.5-1.8 Gy fractions[26][27][28]. However, in adult Hodgkin lymphoma, 2 Gy fractions are standard[29].In addition, the boost dose per fraction is also 2 Gy in the EuroNet protocol (level 2).…”
mentioning
confidence: 99%
“…As per protocol, 30 Gy were delivered to the mediastinum based on the insufficient early response after two OEPA courses. A recent study confirmed an adverse prognostic value of a strongly enhanced residual 18 FDG uptake in early PET-response for treatment outcome [13]. Adversely, the disease was overstaged to Lugano stage IV instead of II based on the positive 18 FDG uptake in the benign enchondroma of the femur that caused initial overtreatment.…”
Section: Discussionmentioning
confidence: 91%